Patterns of Mandibular Invasion in Oral Squamous Cell Carcinoma (Journal of Dentistry and Allied Science, 2024)
Background: Mandibular resections are routinely carried out for achieving a tumor free resection margin for oral cancers. However, the need of mandibular resection to achieve this has always been questioned. The present study was carried out to assess the patterns of mandibular involvement in carcinoma of the mandibular region. Methodology: A total of 23 consecutive patients who had undergone mandibular resection and were found to have mandibular invasion were studied in a prospective open fashion. After decalcification, the specimens were serially sectioned at a 0.5-1 cm interval to identify gross invasion and .3 to .5 micron cut by microtome to identify pattern of mandibular invasion. Preoperative contrast enhanced CT scan was also used to record and analyze the type of invasion. Result: Two types of invasion pattern were found: “erosive” and “invasive”. Out of 23 patients, the mandibular pattern of invasion was infiltrative (invasive) in 7 (30.4 percent) and erosive in 7 (30.4 percent) and no invasion in 9 (39.1 percent). In 6/7 cases of perineural invasion (or 75% of all cases), there was an infiltrative (invasive) trend. The contrast-enhanced computed tomography scan revealed 8 (34.8%) erosive bone involvement, 5 (21.7%) infiltrative (invasive) disease, and 10 (43.5%) no involvement of bone in the 23 individuals investigated. CECT's sensitivity, specificity, NPV, PPV, and accuracy were respectively 71.4%, 66.7%, 60.9%, 76.4%, and 70%. Conclusions: Larger or higher TNM staged tumors are more likely to invade the mandible and show the more aggressive (invasive) form of tumor spread. The accuracy of identifying mandibular invasion by CECT was 70%, indicating a certain degree of sampling error and variability in interpretation.Journal of Dentistry and Allied Science, Vol. 7 No 1: 16-24